2016
DOI: 10.1002/fuce.201600015
|View full text |Cite
|
Sign up to set email alerts
|

Fluorenyl‐containing Quaternary Ammonium Poly(arylene ether sulfone)s for Anion Exchange Membrane Applications

Abstract: A series of anion exchange membranes (AEM) based on block quaternary ammonium poly(arylene ether sulfone) (QA‐bPAES) were successfully synthesized from 9,9′‐bis(4‐hydroxyphenyl) fluorene, 4,4′‐(hexafluoroisopropylidene) diphenol and 4,4′‐difluorodiphenyl sulfone via block polymerization, chloromethylation, quaternization, alkalization and solution casting. Properties of the obtained QA‐bPAES membranes, including ion exchange capacity (IEC), water uptake, swelling ratios, methanol permeability and ion conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…The alkaline stability is significantly enhanced compared with thecontrast QA-PE-CO that containing CO linkages. As shown in Figure , comparing with other novel main chain architecture AEMs reported recently, ,,,,, the QA-PE-NH 2 AEMs developed in this work achieve better alkaline stability and conductivity.…”
Section: Results and Discussionsupporting
confidence: 52%
“…The alkaline stability is significantly enhanced compared with thecontrast QA-PE-CO that containing CO linkages. As shown in Figure , comparing with other novel main chain architecture AEMs reported recently, ,,,,, the QA-PE-NH 2 AEMs developed in this work achieve better alkaline stability and conductivity.…”
Section: Results and Discussionsupporting
confidence: 52%
“…This confirmed the successful synthesis of CMPFAE‐1.94. In general, the chloromethyl groups will be connected to both the main and side phenyl rings of the fluorenyl segments, however, the chloromethyl groups were introduced only to the side phenyl rings of the fluorenyl moieties here. The difference with other researches may be caused by the strong electronegativity of fluorines on the backbone, which reduced the electron density of the main phenyl rings of the fluorenyl moieties.…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, the weight loss was higher for the membrane with higher IEC level. At room temperature, the QPFAE membranes can keep their integrity over 48 h, QPFAE‐1.20 and QPFAE‐0.95 even can keep more than 120 h. The oxidative stability of the obtained QPFAE membranes was superior to the QPAE membranes quaternized in the fluorene moieties but containing no fluorine segments, the existence of strong electronegative fluorides obviously could protect the polymer skeleton from radical attack.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization is not only conducive to the molecular structure design of polymers but also more convenient to introduce novel functional groups to improve the conductivity and chemical stability of the AEMs. Most of the early synthesized AEMs contain heteroatoms such as S atoms, O atoms, and N atoms on the main chain. Although the conductivity of these AEMs has exceeded 100 mS cm –1 , studies have found that the polymer main chain is prone to rupture when the hydroxyl group attacks the heteroatoms, which greatly weakens the alkali resistance of the membrane. For instance, the conductivity of the poly­(ether sulfone) membrane in 1 M KOH solution at 60 °C will be halved in 20 days. , Therefore, polymers without a heteroatom backbone arouse the interest of researchers, including mainly poly­(olefin)­s and ether-free aromatic polymers. The synthesis of poly­(olefin)­s is mainly through the ring-opening metathesis polymerization (ROMP) of small-molecular olefins with catalysts, initiators, , or ultraviolet rays. , This type of AEM possesses not only excellent conductivity but also excellent alkali resistance.…”
Section: Introductionmentioning
confidence: 99%